Conducting Polymers for Tissue Engineering - Guo, Baolin; Ma, Peter X (Biomacromolecules, 2018)
Electrically conducting polymers such as polyaniline, polypyrrole, polythiophene, and their derivatives (mainly aniline oligomer and poly(3,4-ethylenedioxythiophene)) with good biocompatibility find wide applications in biomedical fields including bioactuators, biosensors, neural implants, drug delivery systems, and tissue engineering scaffolds. This review focuses on these conductive polymers for tissue engineering applications. Conductive polymers exhibit promising conductivity as bioactive scaffolds for tissue regeneration, and their conductive nature allows cells or tissue cultured on them to be stimulated by electrical signals. However, their mechanical brittleness and poor processability restrict their application. Therefore, conductive polymeric composites based on conductive polymers and biocompatible biodegradable polymers (natural or synthetic) were developed. The major objective of this review is to summarize the conductive biomaterials used in tissue engineering including conductive composite films, conductive nanofibers, conductive hydrogels, and conductive composite scaffolds fabricated by various methods such as electrospinning, coating, or deposition by in situ polymerization. Furthermore, recent progress in tissue engineering applications using these conductive biomaterials including bone tissue engineering, muscle tissue engineering, nerve tissue engineering, cardiac tissue engineering, and wound healing application are discussed in detail.